USE OF ARTIFICIAL INTELLIGENCE TOOLS IN DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE TEACHERS IN THE CONTEXT OF DIGITAL TRANSFORMATION - Aslanova Sanobar Sulaymanovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article analyzes the role of artificial intelligence (AI) tools in the formation of professional competence of future teachers in the process of digital transformation. Changes in the modern education system require teachers not only to know their subject, but also to have technological and adaptive skills. The study highlights the potential of AI tools in improving personalized learning, automated assessment, and pedagogical design. It also outlines the methodological foundations for improving the digital literacy of future teachers and preparing them to work in an intellectual educational environment. At the end of the article, proposals are made for integrating AI technologies into the curricula of pedagogical higher education institutions.